THE INFLUENCE OF MARKETING COMMUNICATION STRATEGY AND DISTINCTIVE DESTINATION ON DESTINATION BRAND EQUITY (STUDY ON CILETUH GEOPARK, SUKABUMI) - Kurniawan Kurniawan (Sosiohumaniora, 2023)
This study aims to examine the effect of marketing communication strategy and distinctive destination on destination brand equity. The research was conducted at Ciletuh Geopark Sukabumi one of the leading tourist destinations, but its contribution to the regional economy is still not high. This research uses a quantitative research approach. The research was carried out on a cross-sectional time horizon, namely in 2023. The research was carried out on the Ciletuh Geopark analysis unit with an observation unit, namely Ciletuh Geopark visitors, totaling 150 respondents, and processed with structural equation modeling (SEM). Data collection techniques were carried out to respondents through a questionnaire using a 5-point Likert scale. The results of the hypothesis testing show that the marketing communication strategy and distinctive destinations have proven to have a significant effect on destination brand equity. These findings provide managerial implications for the managers of the Ciletuh Geopark to pay more attention to the development of distinctive destinations, especially in terms of culinary development by stimulating the creation of distinctive food and beverage products that characterize the uniqueness of the Ciletuh Geopark. Destination managers also need to pay more attention to the attractiveness of online content and social communication on websites, pay attention to and follow up on online reviews from visitors, and develop content on Facebook and YouTube channels that are more attractive and unique which can encourage greater involvement from visitors.